Effects of the austenitizing temperature on the microstructure and mechanical properties in multiple-phase medium Mn steel. (8th January 2020) - Yang, Yonggang; Mi, Zhenli; Jiang, Haitao; Wang, Mai; Xiu, Qi; Zhang, Yun; Tian, Shiwei; Zhang, Guihua
Abstract: Medium Mn steel (MMnS) is the good choice for car manufacturers to meet the requirements of reducing the weight of automobiles. Quenching & Partitioning (Q&P) process is an effective method to stabilize austenite in advanced steel, thus prompting the comprehensive mechanical properties of advanced steel. In this article, the Q&P process is applied to the MMnS to explore potential mechanical properties. The effect of austenitizing temperature, one of the significant parameters of Q&P process, on the microstructure and mechanical properties of MMnS was investigated. According to microstructural analyse results, all of the MMnS specimens processed by Q&P treatment with different austenitizing temperatures could obtain multi-phase microstructure, including α ′-martensite, ε -martensite and austenite. Furthermore, the highest volume fraction of austenite was observed in the MMnS processed by Q&P treatment at the austenitizing temperature of 920 °C. Due to the facilitated transformation-induced plasticity effect resulted from the high volume fraction of austenite with the austenitizing temperature of 920 °C, the MMnS obtained the high strength, high plasticity and sustaining work-hardening rate.